Knowledge and Acceptability of Long-Acting Reversible Contraception Among Adolescent Women Receiving School-Based Primary Care Services - Andrea J. Hoopes; Kym R. Ahrens; Kelly Gilmore; Janet Cady; Wren L. Haaland; Anne-Marie Amies Oelschlager; Sarah Prager (SAGE Publishing, 2016)
Background: A key strategy to reduce unintended adolescent pregnancies is to expand access to long-acting reversible contraceptive (LARC) methods, including intrauterine devices and subdermal contraceptive implants. LARC services can be provided to adolescents in school-based health and other primary care settings, yet limited knowledge and negative attitudes about LARC methods may influence adolescents' utilization of these methods. This study aimed to evaluate correlates of knowledge and acceptability of LARC methods among adolescent women at a school-based health center (SBHC). Methods: In this cross-sectional study, female patients receiving care at 2 SBHCs in Seattle, Washington completed an electronic survey about sexual and reproductive health. Primary outcomes were (1) LARC knowledge as measured by percentage correct of 10 true-false questions and (2) LARC acceptability as measured by participants reporting either liking the idea of having an intrauterine device (IUD)/subdermal implant or currently using one. Results: A total of 102 students diverse in race/ethnicity and socioeconomic backgrounds completed the survey (mean age 16.2 years, range 14.4-19.1 years). Approximately half reported a lifetime history of vaginal sex. Greater LARC knowledge was associated with white race (regression coefficient [coef] = 26.8; 95% CI 13.3-40.4; P < .001), history of vaginal intercourse (coef = 29.9; 95% CI 17.1-42.7; P < .001), and current/prior LARC use (coef = 22.8; 95% CI 6.5-40.0; P = .007). Older age was associated with lower IUD acceptability (odds ratio = 0.53, 95% CI 0.30-0.94; P = .029) while history of intercourse was associated with greater implant acceptability (odds ratio 5.66, 95% CI 1.46-22.0; P = .012). Discussion: Adolescent women in this SBHC setting had variable knowledge and acceptability of LARC. A history of vaginal intercourse was the strongest predictor of LARC acceptability. Our findings suggest a need for LARC counseling and education strategies, particularly for young women from diverse cultural backgrounds and those with less sexual experience.